The importance of the multidisciplinary team in complex surgeries (International Seven Journal of Multidisciplinary, 2024)
Stem cells, Stem cell research, The need for a multidisciplinary team when performing various types of surgery is obvious. And this article addresses the importance of the multidisciplinary team in more complex surgeries, highlighting the benefits of a collaborative approach in the effective and safe management of patients undergoing challenging surgical procedures such as organ transplants, tumor removal, bariatric surgery and other surgeries. The review examines the specific roles of different medical specialties, psychologists, nutritionists, physiotherapists, nurses and other healthcare professionals, who have their specific role in the multidisciplinary team, the positive impacts on reducing complications and improving clinical outcomes, as well as the importance of communication and coordination between team members. The main objectives of the research are to identify which specialties and professionals make up the multidisciplinary team and their main functions in the context of more complex surgeries. As well as to identify whether there really needs to be adequate communication in order for procedures to be carried out properly. We conclude by highlighting the ongoing need to value and promote multidisciplinary collaboration in order to guarantee the best possible care for patients in preparation for surgery, pre-surgery, intra-surgery, post-surgery and rehabilitation. Diabetes Mellitus, Nursing care, Therapeutics.